Street-Frequenting Young People in Fiji Theory and Practice - Vakaoti, Patrick (Springer International Publishing, 2018)
This book, uncovers the lived experiences of street-frequenting young people in Fiji. Typically viewed as 'out of place', these young people disturb what it means to be young and Fijian. Despite their marginal existence, they through their activities demonstrate the need to belong. The book adopts a critical postmodern perspective to explore this reality and propose ways of engaging with street-frequenting young people. Candidly written, Street-Frequenting Young People in Fiji identifies issues that provoke the conscience of Fijian hierarchy and its leaders. It will appeal to students and scholars across a range of disciplines- including sociology, childhood and youth studies, and social work- as well as practitioners and policy analysts.